Referencing of powder bed for in situ detection of lateral layer displacements in additive manufacturing - Lerchen, Martin; Schinn, Julien; Hausotte, Tino (Journal of Sensors and Sensor Systems, 2021)
An increasing number of additive manufacturing (AM) applications leads to rising challenges for the processaccompanying quality assurance. Beside post-processing measurement systems, in situ monitoring systems in particular are currently requested to ensure feedback controlling during AM processes. For data acquisition and subsequent evaluation a high data quality is of importance. It depends on a high resolution and accuracy of measurement systems, adapted measurement conditions and a reference to the powder bed or component for geometric measurements. Within this scientific study, a new reference system has been implemented into the powder bed to reduce measurement deviations by an abbreviated metrological loop. After data acquisition and image processing layer by layer, the position stability of the reference system has been analysed in relation to the optical measuring system. Based on a contour detection of the reference markers, the evaluation of geometrical process deviations is presented as an essential basis for a closed-loop controlling system. Thermally induced and mechanical drifts within the manufacturing process can be verified by the reference system in the powder bed. As an outlook two methods are suggested for a process-accompanying referenced detection of the melting pool and resulting contour displacements during additive manufacturing.<br
Projekt ID 61375930 - Teilprojekt C4
Keywords: Additive manufacturing (AM); laser beam melting (LBM); reference system; metrological circuit; optical in situ monitoring; lateral displacements